2013
DOI: 10.1002/ps.3537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sunlight-exposed pyrethroid-treated netting for the control of face fly and housefly (Diptera: Muscidae)

Abstract: With careful choice of the pyrethroid applied, treated netting could be an important component of livestock integrated pest management programs focused on sustainable practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…More importantly, the pyrethroid treated netting (Zero Fly livestock fence) has been recently introduced and being regarded as affordable by poor farmers, easy to transport and relatively safe for the user and the environment. Thus it can be used as an alternative tool to combat against fly challenges and vector born livestock diseases (Baur et al, 2011;Maia et al, 2012;Peck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the pyrethroid treated netting (Zero Fly livestock fence) has been recently introduced and being regarded as affordable by poor farmers, easy to transport and relatively safe for the user and the environment. Thus it can be used as an alternative tool to combat against fly challenges and vector born livestock diseases (Baur et al, 2011;Maia et al, 2012;Peck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was necessary to keep the investigational LLINs under ideal temperature and humidity conditions, as it is known that high temperature may inactivate the insecticide or binder [19,26]. Proper storage should also avoid direct sunlight as pyrethroids are decomposed by UV light and heat [27].…”
Section: Discussionmentioning
confidence: 99%
“…Atieli et al showed that drying methods used after washing nets, resulted in significant impact on the efficacy of pyrethroid nets: nets washed 20 times and dried under the shade retained more pyrethroid insecticide (62.5%) than nets directly dried under the sunlight (58.8%) [20]. Furthermore, Peck et al reported that the insecticidal activity of the pyrethroid Lambda-cyhalothrin was reduced after 10 weeks of exposure to direct sunlight [26].…”
Section: Discussionmentioning
confidence: 99%
“…Atieli et al (2010), showed that drying methods used after washing nets, resulted in significant impact on the efficacy of pyrethroid nets: nets washed 20 times and dried under the shade retained more pyrethroid insecticide (62.5%) than nets directly dried under the sunlight (58.8%) [20]. Furthermore, Peck et al (2014) reported that the insecticidal activity of the pyrethroid Lambda-cyhalothrin was reduced after 10 weeks of exposure to direct sunlight [26].…”
Section: Discussionmentioning
confidence: 99%